2016
DOI: 10.1038/ncomms13720
|View full text |Cite
|
Sign up to set email alerts
|

The tumour microenvironment harbours ontogenically distinct dendritic cell populations with opposing effects on tumour immunity

Abstract: Various steady state and inflamed tissues have been shown to contain a heterogeneous DC population consisting of developmentally distinct subsets, including cDC1s, cDC2s and monocyte-derived DCs, displaying differential functional specializations. The identification of functionally distinct tumour-associated DC (TADC) subpopulations could prove essential for the understanding of basic TADC biology and for envisaging targeted immunotherapies. We demonstrate that multiple mouse tumours as well as human tumours h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
264
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(282 citation statements)
references
References 56 publications
8
264
1
1
Order By: Relevance
“…S1D). These phenotypes are consistent with those described for CD11b + and CD11b - CD103 + conventional DC subsets in normal (40) and tumor (41, 42) tissues, and distinct from those described for F4/80 + CD24 lo CD64 + Mφ /TAM (41). Thus, we will henceforth refer to the CD11b +/- CD11c hi MHC-II hi populations as CD11b + and CD11b - DC.…”
Section: Resultssupporting
confidence: 88%
“…S1D). These phenotypes are consistent with those described for CD11b + and CD11b - CD103 + conventional DC subsets in normal (40) and tumor (41, 42) tissues, and distinct from those described for F4/80 + CD24 lo CD64 + Mφ /TAM (41). Thus, we will henceforth refer to the CD11b +/- CD11c hi MHC-II hi populations as CD11b + and CD11b - DC.…”
Section: Resultssupporting
confidence: 88%
“…In some settings, however, IFN-g may switch monocyte differentiation from DCs to macrophages (38). Reports of other studies have shown that monocyte-derived tumor DCs suppress CTL proliferation (14), which was linked to their expression of iNOS and production of NO. In our study, ∼50% of DC3 express iNOS in both WT and Zbtb46-DTR bone marrow chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…The success of PD-1-based immunotherapies depends on CD28 costimulation by B7-expressing tumor APCs to promote T cell expansion and prevent T cell exhaustion (45,46). Given the natural abundance of tumor DC3 in various human cancers (14), they provide an additional therapeutic target to boost antitumor immune responses. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73,103 In addition, the tumor microenvironment may have major impact on the production of functionally and phenotypically different DC subsets. 27,28,104,105 It will be intriguing to investigate under these inflammatory conditions whether and how epigenetic effects may help immune cells to adopt previously recognized phenotype and functions, thereby influencing overall consequence of immune responses.…”
Section: Resultsmentioning
confidence: 99%